1999
DOI: 10.1071/ar98087
|View full text |Cite
|
Sign up to set email alerts
|

Prior crop and residue incorporation time affect the response of paddy rice to fertiliser nitrogen

Abstract: Crop residues are an important source of nitrogen (N) for rice (Oryza sativa L.). The objective of this research was to determine how the supply of mineral N from different prior crops or fallow might affect the growth and yield of rice. The study also tested whether N use by rice might be improved by timing the application of inorganic fertiliser N to supplement the N mineralised after prior crops. Experiments consisted of fallow, or cereal or legume crops in the dry-season followed by wet-season rice; and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…The results also show that root residue averaged 11.9 % of the total soya bean dry matter at harvest maturity (including grain). This value is close to the 10.5 % obtained in Australia by Ockerby et al. (1999).…”
Section: Root Residuesupporting
confidence: 89%
See 1 more Smart Citation
“…The results also show that root residue averaged 11.9 % of the total soya bean dry matter at harvest maturity (including grain). This value is close to the 10.5 % obtained in Australia by Ockerby et al. (1999).…”
Section: Root Residuesupporting
confidence: 89%
“…The results also show that root residue averaged 11.9 % of the total soya bean dry matter at harvest maturity (including grain). This value is close to the 10.5 % obtained in Australia by Ockerby et al (1999). Relative to the root residue of 0.35 Mg ha )1 in the early variety, root residue was significantly higher by 87-106 % in the late varieties.…”
Section: Root Residuesupporting
confidence: 85%
“…The data in this paper were obtained from 3 experiments conducted between 1988 and1990 at Millaroo Research Station, Queensland Department of Primary Industries (20°03ЈS, 147°17ЈE), in northern Queensland, Australia. Full details of the experimental procedures are reported by Ockerby et al (1999). The experiments measured the uptake and use of N by wet-season (DecemberApril) or dry-season (JulyDecember) rice (cv.…”
Section: Treatments and Experimental Designmentioning
confidence: 99%
“…Rice is a determinate species and both the amount and timing of N uptake may affect yield. In a concurrent paper, Ockerby et al (1999) reported that the responses of rice dry weight, yield, and harvest index to fertiliser N were modified by prior fallow and crop treatments. Other work by Buresh and De Datta (1991) and Buresh et al (1993) also suggested that rice yield responses to the time when fertiliser N is applied may be dependent on whether crop residues were incorporated before transplanting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation